Fullerene composite material, preparation method thereof and application of fullerene composite material as solid-state hydrogen storage material

CN122916044APending Publication Date: 2026-10-16CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611026454.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

石墨本身几乎不具备储氢能力,其规整的层状微观结构对氢分子的物理吸附与固定作用极弱,无法为氢分子存储提供有效吸附位点

Benefits of technology

本发明利用富勒烯独特的三维笼状中空结构,可有效吸附、固定氢分子,主动参与储氢过程。富勒烯替代石墨作为填充剂后,彻底消除了惰性填充组分对储氢体系容量的制约,显著提升固态储氢材料的整体质量储氢密度与体积储氢密度,从而显著提高固态储氢材料的储氢量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916044A_ABST
    Figure CN122916044A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid-state hydrogen storage materials, and particularly relates to a fullerene composite material, a preparation method thereof and application of the fullerene composite material as a solid-state hydrogen storage material. The fullerene and a metal-based solid-state hydrogen storage base material are mixed and then ball-milled to obtain a composite material; the composite material is pressure-formed to obtain a formed body; and the formed body is heat-treated to obtain the fullerene composite material. The application uses fullerene to replace traditional graphite as a modified filler of the solid-state hydrogen storage material, and cooperates with ball-milling, pressure forming and surface treatment processes to comprehensively improve the comprehensive performance of the solid-state hydrogen storage material. The fullerene composite material provided by the application has strong structural stability, and the hydrogen storage capacity and hydrogen storage rate are significantly improved. In addition, the fullerene composite material has good durability in the hydrogen absorption and release cycle process, a long service life, and important engineering application value and industrial promotion significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid hydrogen storage materials technology, specifically relating to a fullerene composite material, its preparation method, and its application as a solid hydrogen storage material. Background Technology

[0002] Hydrogen energy, as a clean and efficient secondary energy source, is a key development direction in the current new energy field. It can effectively solve the environmental pollution and resource shortage problems caused by traditional fossil fuels, and has broad application prospects in energy storage, transportation, and industrial manufacturing. Hydrogen storage technology is the core and key link in the large-scale promotion and application of hydrogen energy. Compared with high-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage technologies, solid-state hydrogen storage technology has become the mainstream research direction of hydrogen storage technology at present due to its outstanding advantages such as high safety, high volumetric hydrogen storage density, good storage stability, and convenient storage and transportation.

[0003] In existing solid-state hydrogen storage material preparation processes, carbon-based fillers are typically added to optimize the overall performance of the hydrogen storage matrix. Among these, graphite, due to its excellent thermal conductivity and structural reinforcing properties, is widely used as a conventional filler component in solid-state hydrogen storage materials. The introduction of graphite can effectively improve the overall thermal conductivity of hydrogen storage composite materials, enhance the heat transfer efficiency during hydrogen absorption and desorption, stabilize the internal microstructure of the material, alleviate structural pulverization and collapse problems that occur during cyclic hydrogen absorption and desorption, improve the overall structural stability of the material, and significantly optimize the basic application performance of solid-state hydrogen storage materials.

[0004] However, existing solid-state hydrogen storage technologies based on graphite-filled modification still have technical defects, which restrict the further upgrading of hydrogen storage material performance. Graphite itself has almost no hydrogen storage capacity; its regular layered microstructure has extremely weak physical adsorption and fixation effects on hydrogen molecules, and cannot provide effective adsorption sites for hydrogen molecule storage. In composite material systems, graphite fillers without hydrogen storage activity exist only as functional auxiliary components, occupying effective space and component proportions within the hydrogen storage material. They cannot participate in hydrogen storage reactions, which greatly limits the improvement of the overall mass and volumetric hydrogen storage density of solid-state hydrogen storage materials. This results in the low hydrogen storage capacity of existing graphite-modified hydrogen storage materials, making it difficult to meet the performance requirements of high-end application scenarios such as large-scale hydrogen energy storage and on-board hydrogen energy supply. Summary of the Invention

[0005] The purpose of this invention is to provide a fullerene composite material, its preparation method, and its application as a solid hydrogen storage material. The fullerene composite material provided by this invention has strong structural stability, significantly improved hydrogen storage capacity and hydrogen storage rate, good durability during hydrogen absorption and desorption cycles, and long service life, and has important engineering application value and industrial promotion significance.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a fullerene composite material, comprising the following steps: Fullerene and metal-based solid hydrogen storage matrix materials were mixed and then ball-milled to obtain a composite material; The composite material is pressure molded to obtain a molded body; The molded body is heat-treated to obtain the fullerene composite material.

[0007] Preferably, the fullerene comprises one or both of C60 and C70; the purity of the fullerene is ≥80%.

[0008] Preferably, before mixing, the fullerene is further subjected to a preheating treatment at a temperature of 200-600°C for a holding time of 1-6 hours. The preheating treatment is carried out under vacuum conditions with a vacuum degree of not less than 0.1 Pa.

[0009] Preferably, the metal-based solid hydrogen storage matrix material includes one or more of a magnesium matrix, a magnesium alloy matrix, a titanium matrix, and a titanium-iron alloy matrix; the particle size of the metal-based solid hydrogen storage matrix material is ≤500μm.

[0010] Preferably, the fullerene accounts for 0.1% to 20% of the mass of the metal-based solid hydrogen storage matrix material.

[0011] Preferably, the ball milling speed is 100~500 r / min and the time is 1~30 h; the pressure forming conditions include: pressure of 1~20 MPa and holding time of 0.5~10 min; the heat treatment temperature is 200~1000℃ and the holding time is 1~5 h.

[0012] Preferably, the initial molded composite material obtained after heat treatment further includes post-treatment of the initial molded composite material to obtain the fullerene composite material; the post-treatment includes surface modification treatment or coating a protective layer treatment, the surface modification treatment includes: depositing a metal coating on the surface of the initial molded composite material by chemical plating, the metal coating including a nickel layer and / or a palladium layer.

[0013] The present invention provides a fullerene composite material prepared by the preparation method described in the above technical solution.

[0014] This invention provides the application of the fullerene composite material described in the above technical solution as a solid hydrogen storage material.

[0015] This invention provides a method for preparing a fullerene composite material, comprising the following steps: mixing fullerene and a metal-based solid hydrogen storage matrix material and then ball milling to obtain a composite material; pressure molding the composite material to obtain a molded body; and heat-treating the molded body to obtain the fullerene composite material. In this invention, fullerene possesses a unique closed cage-like microstructure, excellent specific surface area, and excellent physicochemical stability, unlike the layered structure of traditional graphite, and can provide a large number of active adsorption sites. This invention addresses the technical shortcomings of existing graphite-filled solid hydrogen storage materials, such as low hydrogen storage capacity and limited performance improvement, by using fullerene to replace traditional graphite as a modifying filler for solid hydrogen storage materials. Combined with ball milling, pressure molding, and surface treatment processes, this achieves a comprehensive improvement in the overall performance of solid hydrogen storage materials. Compared with existing technologies, this invention has the following significant advantages: This invention utilizes the unique three-dimensional cage-like hollow structure of fullerenes, which can effectively adsorb and immobilize hydrogen molecules, actively participating in the hydrogen storage process. By replacing graphite as a filler, fullerenes completely eliminate the constraint of inert filler components on the capacity of the hydrogen storage system, significantly improving the overall mass and volumetric hydrogen storage density of solid-state hydrogen storage materials, thereby significantly increasing the hydrogen storage capacity of solid-state hydrogen storage materials.

[0016] In this invention, fullerenes and metal-based solid hydrogen storage matrix materials can form a good composite coupling effect, which can effectively optimize the entire process of hydrogen molecule adsorption, dissociation, and desorption. Compared with the single physical bonding between graphite and the matrix, the special structure of fullerenes can reduce the hydrogen molecule adsorption energy barrier and weaken the hydrogen adsorption binding strength. This ensures the stable storage of hydrogen molecules while facilitating the rapid desorption and release of hydrogen molecules, effectively improving the hydrogen storage rate and hydrogen release efficiency of the material, and significantly optimizing the hydrogen storage kinetics performance of solid hydrogen storage materials, making them suitable for practical applications of rapid hydrogen charging and discharging.

[0017] This invention utilizes a combined pressure forming and heat treatment process to make the composite system formed by fullerene and metal-based solid hydrogen storage matrix more compact, effectively reducing and eliminating excess pores and defects within the composite material, and optimizing the material's microstructure. Simultaneously, the specific interfacial interaction between fullerene and metal-based solid hydrogen storage matrix further strengthens the composite interface bond strength, effectively suppressing structural pulverization, cracking, and collapse caused by hydrogen-induced expansion and contraction during multiple hydrogen absorption and desorption cycles. This significantly improves the structural integrity and stability of the material during recycling, greatly enhancing the cycle durability of the hydrogen storage material.

[0018] Furthermore, this invention employs surface modification treatment or coating with a protective layer to form a uniform and dense protective layer on the surface of the fullerene-modified hydrogen storage composite material. This protective structure effectively isolates the hydrogen storage matrix from the erosion of air, moisture, and corrosive media, preventing oxidation and failure of the metal-based solid hydrogen storage matrix material. Simultaneously, it buffers structural stress loss during hydrogen absorption and desorption, comprehensively improving the chemical stability and corrosion resistance of the material, effectively extending the service life of solid hydrogen storage materials, reducing the operation, maintenance, and replacement costs of hydrogen energy storage equipment, and enhancing the industrial application value of the technology. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the preparation process for improving the hydrogen storage capacity of solid hydrogen storage materials in an embodiment of the present invention. Detailed Implementation

[0020] This invention provides a method for preparing a fullerene composite material, comprising the following steps: Fullerene and metal-based solid hydrogen storage matrix materials were mixed and ball-milled to obtain a composite material; The composite material is pressure molded to obtain a molded body; The molded body is heat-treated to obtain the fullerene composite material.

[0021] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.

[0022] This invention involves ball milling a mixture of fullerene and a metal-based solid hydrogen storage matrix material to obtain a composite material. In this invention, the fullerene preferably comprises one or both of C60 and C70. When the fullerene is preferably C60 and C70, the mass ratio of C60 to C70 is preferably (1~2):(1~2). The purity of the fullerene is preferably ≥80%, more preferably ≥85%, and in the examples, it can be 91.2% or 85.2%. In this invention, the fullerene serves as a filler, and its purity is crucial for its hydrogen storage performance and dispersibility in the solid hydrogen storage material. However, purity is also linked to cost. This invention comprehensively considers multiple factors such as purity, hydrogen storage increment, and cost, and preferably uses a fullerene purity of ≥80%.

[0023] In this invention, prior to mixing, the fullerene is preferably preheated. The preheating temperature is preferably 200-600°C, and in the embodiments, it can be 200°C or 400°C; the holding time is preferably 1-6 hours, and in the embodiments, it can be 3 hours or 5 hours. The preheating is preferably performed under vacuum conditions, with a vacuum degree preferably not less than 0.1 Pa, more preferably not less than 0.05 Pa, and even more preferably not less than 0.01 Pa. This invention preferably removes impurities and moisture adsorbed on the surface of the fullerene by preheating, thereby improving the surface activity of the fullerene.

[0024] In this invention, the metal-based solid hydrogen storage matrix material preferably includes one or more of the following: a magnesium matrix, a magnesium alloy matrix, a titanium matrix, and a titanium-iron alloy matrix. The magnesium matrix is ​​magnesium powder (purity ≥ 99.5%). The titanium matrix is ​​titanium powder (purity ≥ 99.5%). The titanium-iron alloy matrix is ​​a titanium-iron-manganese alloy. The titanium-iron-manganese alloy can be Ti48Fe42Mn10.

[0025] In this invention, the particle size of the metal-based solid hydrogen storage matrix material is preferably ≤500μm, more preferably ≤350μm, even more preferably ≤200μm, and even more preferably ≤150μm. In the embodiments, it can be ≤80μm or 20~120μm.

[0026] In this invention, the percentage of the fullerene by mass of the metal-based solid hydrogen storage matrix material is preferably 0.1-20%, more preferably 0.5-10%, and in the examples 0.5% or 3%.

[0027] In this invention, the ball milling is performed in a high-energy ball mill. The preferred milling speed is 100-500 r / min, more preferably 200-400 r / min, and in the embodiments, it can be 300 r / min or 400 r / min. The preferred milling time is 1-30 h, more preferably 5-30 h, and in the embodiments, it can be 8 h or 10 h. In this invention, during the ball milling process, fullerenes and the metal-based solid hydrogen storage matrix material collide and rub against each other, achieving uniform mixing. Simultaneously, fullerenes may embed into the surface or interior of the metal-based solid hydrogen storage matrix material particles, forming a certain interfacial interaction.

[0028] After obtaining the composite material, the present invention performs pressure molding on the composite material to obtain a molded body. Preferably, the composite material is placed in a hot press mold for pressure molding. In the present invention, the pressure molding conditions include: a pressure preferably of 1~20 MPa, more preferably 3~17 MPa, and in the embodiments, 5 MPa or 15 MPa; a holding time preferably of 0.5~10 min, more preferably 1~8 min, and in the embodiments, 5 min or 2 min. The present invention prepares a solid hydrogen storage material of the desired shape through pressure molding. In the present invention, pressure molding can make the composite material more compact, reduce the porosity inside the material, and improve the structural stability and thermal conductivity of the material.

[0029] After obtaining the molded body, the present invention performs heat treatment on the molded body to obtain the fullerene composite material. In the present invention, the heat treatment temperature is preferably 200~1000℃, more preferably 300~900℃, and in the embodiments it can be 350℃ or 800℃; the holding time is preferably 1~5h, and in the embodiments it can be 1h or 3h. The present invention heat-treats the molded body under the above-mentioned temperature (200~1000℃) and holding time (1~5h) conditions, which can effectively mitigate the impact of volume expansion of the composite material in hydrogen absorption and desorption cycles on the hydrogen storage material.

[0030] In this invention, the initial molded composite material obtained after heat treatment is further subjected to post-treatment to obtain the fullerene composite material. Preferably, the post-treatment includes surface modification or coating with a protective layer. This invention, through post-treatment, further improves the interfacial bonding strength and hydrogen storage performance between fullerene and the metal-based solid hydrogen storage matrix material.

[0031] In this invention, the surface modification treatment preferably includes: depositing a metal coating on the surface of the initially formed composite material using a chemical plating method, wherein the metal coating includes a nickel layer and / or a palladium layer. In this invention, the metal coating acts as a catalyst, promoting the dissociation and adsorption of hydrogen molecules, while simultaneously enhancing the interaction between fullerenes and the metal-based solid hydrogen storage matrix material. In this invention, the plating solution used for chemical plating preferably includes a nickel plating solution and / or a palladium plating solution. The composition of the nickel plating solution preferably includes: 20-30 g / L nickel sulfate (preferably 26 g / L), 15-20 g / L sodium hypophosphite (preferably 20 g / L), 10-20 g / L sodium citrate (preferably 15 g / L), and 5-15 g / L sodium acetate (preferably 10 g / L). The pH value of the nickel plating solution is preferably 5.0-5.5. The chemical plating conditions preferably include: a temperature of 80-85°C and a plating time of 35-45 min, which can be 40 min in the examples. The thickness of the metal coating is preferably 0.1~1.5μm, more preferably 0.3~1μm, and in the embodiment it can be 0.5μm.

[0032] This invention does not have specific requirements for the specific implementation of the protective coating treatment. This invention, through the protective coating treatment, can prevent the expansion and pulverization of the hydrogen storage material. In this invention, during the hydrogen absorption and desorption process of the hydrogen storage material, the metal-based solid hydrogen storage matrix material will gradually exhibit pulverization. This invention, by coating a protective layer onto the solid hydrogen storage material after molding, can, to a certain extent, prevent the pulverization phenomenon from causing the hydrogen storage material to disintegrate.

[0033] The present invention provides a fullerene composite material prepared by the preparation method described in the above technical solution.

[0034] This invention provides the application of the fullerene composite material described in the above technical solution as a solid hydrogen storage material.

[0035] To further illustrate the present invention, the technical solutions provided by the present invention are described in detail below with reference to embodiments, but these should not be construed as limiting the scope of protection of the present invention. The following embodiments are based on... Figure 1 The preparation process is illustrated in the example.

[0036] Example 1 This embodiment provides a method for preparing a solid hydrogen storage material, specifically including the following steps: 1. Material selection: Pure magnesium powder with a purity of 91.2% C60 and a particle size ≤80μm was selected as the matrix material; 2. Pretreatment: Fullerene (C60) was treated at 400℃ for 3 hours under vacuum conditions with a vacuum degree not lower than 0.01 Pa; 3. Preparation of composite materials: Pretreated C60 and pure magnesium powder were placed in a high-energy ball mill. The mass of C60 accounted for 3% of the mass of pure magnesium powder. The mixture was ball-milled at 300 rpm for 10 hours and then pressure-molded at 5 MPa for 2 min. 4. Heat treatment: The molded composite material is heat treated, specifically by holding it at 350℃ for 1 hour; 5. Performance Optimization: A layer of nickel was plated onto the surface of the composite material obtained in step 4 using a chemical plating method. Specifically, the composite material after heat treatment in step 4 was placed in a chemical nickel plating solution. The chemical nickel plating solution consisted of 26 g / L nickel sulfate, 20 g / L sodium hypophosphite, 15 g / L sodium citrate, and 10 g / L sodium acetate. The pH value was controlled at 5.0, the temperature was 85℃, the plating time was 40 minutes, and the nickel plating layer thickness was 0.5 μm, thus obtaining a solid hydrogen storage material.

[0037] 6. Performance testing: The hydrogen storage performance of the solid hydrogen storage material prepared in this embodiment was tested using a Siefverts device. Under the conditions of 300℃ and 3MPa, the hydrogen storage capacity of the fullerene composite material prepared in this embodiment reached 5.58wt%.

[0038] Comparative Example 1 The preparation method is basically the same as that in Example 1, except that graphite is used instead of fullerene (C60) to prepare the hydrogen storage material. Following the method in step 6 of Example 1, the hydrogen storage capacity of the graphite composite material prepared in Comparative Example 1 was measured to be 5.12 wt%.

[0039] The solid hydrogen storage material (fullerene composite material) prepared in Example 1 has a hydrogen storage capacity that is about 9% higher than that of the solid hydrogen storage material (graphite composite material) prepared in Comparative Example 1.

[0040] Example 2 This embodiment provides a method for preparing a solid hydrogen storage material, specifically including the following steps: 1. Material selection: Ti48Fe42Mn10 titanium-iron-manganese alloy with a purity of 85.2% (mass ratio 1:1) and a particle size of 20~120 micrometers was selected as the matrix material. 2. Pretreatment: Fullerenes (C60 and C70) were treated at 200°C for 5 hours under vacuum conditions, with a vacuum degree of not less than 0.05 Pa; 3. Preparation of composite materials: Pretreated fullerenes (C60 and C70) and titanium-iron-manganese alloy Ti48Fe42Mn10 were placed in a high-energy ball mill. The mass of fullerenes (C60 and C70) accounted for 0.5% of the mass of titanium-iron-manganese alloy Ti48Fe42Mn10. The mixture was ball-milled at 400 rpm for 8 hours, and then pressure-molded at 15 MPa for 5 min. 4. Heat treatment: The molded composite material is heat treated at 800℃ for 3 hours to obtain solid hydrogen storage material.

[0041] 5. Performance testing: The hydrogen storage performance of the solid hydrogen storage material prepared in this embodiment was tested using a Siefverts device. Under the conditions of 120°C and 1 MPa, the hydrogen storage capacity of the fullerene composite material prepared in this embodiment as a solid hydrogen storage material reached 1.68 wt%.

[0042] Comparative Example 2 The preparation method is basically the same as that in Example 2, except that graphite is used instead of fullerene (C60) to prepare the hydrogen storage material. Following the method in step 5 of Example 2, the hydrogen storage capacity of the graphite composite material prepared in Comparative Example 2 was measured to be 1.45 wt%.

[0043] The solid hydrogen storage material (fullerene composite material) prepared in Example 2 has a hydrogen storage capacity that is about 15.9% higher than that of the solid hydrogen storage material (graphite composite material) prepared in Comparative Example 2.

[0044] As demonstrated by the above embodiments, the fullerene composite material provided by this invention, as a solid-state hydrogen storage material, leverages the unique cage-like structure of fullerenes to provide more hydrogen molecule adsorption sites compared to graphite fillers, thereby significantly increasing the hydrogen storage capacity of the solid-state hydrogen storage material. Simultaneously, the composite effect between fullerenes and the hydrogen storage matrix optimizes the adsorption and storage process of hydrogen molecules, reducing adsorption energy and increasing the hydrogen storage rate. This invention utilizes pressure molding and heat treatment processes to make the composite material more dense, reducing internal porosity. Furthermore, the interaction between fullerenes and metal hydrides helps enhance the structural stability of the material, improving its durability during hydrogen absorption and desorption cycles. This invention, through coating a protective layer and surface modification processes, can improve the stability and corrosion resistance of the solid-state hydrogen storage material, extending its service life.

[0045] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a fullerene composite material, characterized in that, Includes the following steps: Fullerene and metal-based solid hydrogen storage matrix materials were mixed and then ball-milled to obtain a composite material; The composite material is pressure molded to obtain a molded body; The molded body is heat-treated to obtain the fullerene composite material.

2. The preparation method according to claim 1, characterized in that, The fullerene includes one or both of C60 and C70; the purity of the fullerene is ≥80%.

3. The preparation method according to claim 1 or 2, characterized in that, Before mixing, the fullerene is preheated at a temperature of 200-600°C for 1-6 hours. The preheating is carried out under vacuum conditions with a vacuum degree of not less than 0.1 Pa.

4. The preparation method according to claim 1, characterized in that, The metal-based solid hydrogen storage matrix material includes one or more of magnesium matrix, magnesium alloy matrix, titanium matrix and titanium-iron alloy matrix; the particle size of the metal-based solid hydrogen storage matrix material is ≤500μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The percentage of the fullerene's mass in the metal-based solid hydrogen storage matrix material is 0.1-20%.

6. The preparation method according to claim 1, characterized in that, The ball milling speed is 100~500 r / min, and the time is 1~30 h; the pressure forming conditions include: pressure of 1~20 MPa, holding time of 0.5~10 min; the heat treatment temperature is 200~1000℃, and the holding time is 1~5 h.

7. The preparation method according to claim 1, characterized in that, The initial molded composite material obtained after heat treatment also includes post-treatment of the initial molded composite material to obtain the fullerene composite material; the post-treatment includes surface modification treatment or coating a protective layer treatment, the surface modification treatment includes: depositing a metal coating on the surface of the initial molded composite material by chemical plating, the metal coating including a nickel layer and / or a palladium layer.

8. The fullerene composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the fullerene composite material according to claim 8 as a solid hydrogen storage material.